If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 10) * 2x = 246 Reorder the terms: 5(10 + x) * 2x = 246 Reorder the terms for easier multiplication: 5 * 2x(10 + x) = 246 Multiply 5 * 2 10x(10 + x) = 246 (10 * 10x + x * 10x) = 246 (100x + 10x2) = 246 Solving 100x + 10x2 = 246 Solving for variable 'x'. Reorder the terms: -246 + 100x + 10x2 = 246 + -246 Combine like terms: 246 + -246 = 0 -246 + 100x + 10x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-123 + 50x + 5x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-123 + 50x + 5x2)' equal to zero and attempt to solve: Simplifying -123 + 50x + 5x2 = 0 Solving -123 + 50x + 5x2 = 0 Begin completing the square. Divide all terms by 5 the coefficient of the squared term: Divide each side by '5'. -24.6 + 10x + x2 = 0 Move the constant term to the right: Add '24.6' to each side of the equation. -24.6 + 10x + 24.6 + x2 = 0 + 24.6 Reorder the terms: -24.6 + 24.6 + 10x + x2 = 0 + 24.6 Combine like terms: -24.6 + 24.6 = 0.0 0.0 + 10x + x2 = 0 + 24.6 10x + x2 = 0 + 24.6 Combine like terms: 0 + 24.6 = 24.6 10x + x2 = 24.6 The x term is 10x. Take half its coefficient (5). Square it (25) and add it to both sides. Add '25' to each side of the equation. 10x + 25 + x2 = 24.6 + 25 Reorder the terms: 25 + 10x + x2 = 24.6 + 25 Combine like terms: 24.6 + 25 = 49.6 25 + 10x + x2 = 49.6 Factor a perfect square on the left side: (x + 5)(x + 5) = 49.6 Calculate the square root of the right side: 7.042726745 Break this problem into two subproblems by setting (x + 5) equal to 7.042726745 and -7.042726745.Subproblem 1
x + 5 = 7.042726745 Simplifying x + 5 = 7.042726745 Reorder the terms: 5 + x = 7.042726745 Solving 5 + x = 7.042726745 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 7.042726745 + -5 Combine like terms: 5 + -5 = 0 0 + x = 7.042726745 + -5 x = 7.042726745 + -5 Combine like terms: 7.042726745 + -5 = 2.042726745 x = 2.042726745 Simplifying x = 2.042726745Subproblem 2
x + 5 = -7.042726745 Simplifying x + 5 = -7.042726745 Reorder the terms: 5 + x = -7.042726745 Solving 5 + x = -7.042726745 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = -7.042726745 + -5 Combine like terms: 5 + -5 = 0 0 + x = -7.042726745 + -5 x = -7.042726745 + -5 Combine like terms: -7.042726745 + -5 = -12.042726745 x = -12.042726745 Simplifying x = -12.042726745Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.042726745, -12.042726745}Solution
x = {2.042726745, -12.042726745}
| 3x*2xy+xy= | | A=6(2x-3)+2(3-2x) | | x^2=100+10x | | 6×1/2-7 | | 2x+35=5x-85 | | 10k=4k-16 | | y=2+3x+6x^2 | | 1/2x=34=48 | | 10x+2(141x)=-2 | | -12c=4c+12 | | 0.2(x+3)+0.5=0.2x-1.1 | | 7k-3k+11= | | 3/4×59×250 | | 8x-13/8=347/72 | | A=10(x-1)-2x | | -4x+14+6x-23=6 | | 3x+4?4=31 | | y=6x^2+3x+2 | | 5x^2-21x=24 | | -1/4b=-1 | | 4(-4x-4)=-8(8+2x) | | x×3/4×5/9=250 | | -6(m+20)=-3 | | 10x=5.3 | | c=5(x-4)+3x+2 | | -6x+9+8x=4 | | 3x+4-2(x+1)=9 | | -6+9+8x=4 | | 8(x+4)=6(x+10) | | -16x^2+40=0 | | 9z-9=-9 | | 10w-6=13w+5 |